2017
DOI: 10.1002/jcph.1041
|View full text |Cite
|
Sign up to set email alerts
|

Delafloxacin Pharmacokinetics in Subjects With Varying Degrees of Renal Function

Abstract: Delafloxacin, a fluoroquinolone, has activity against gram‐positive organisms including methicillin‐resistant Staphylococcus aureus and fluoroquinolone‐susceptible and –resistant gram‐negative organisms. This study was conducted to determine delafloxacin pharmacokinetics after a single intravenous infusion or oral dose administration in subjects with varying degrees of renal function. The study was an open‐label, parallel‐group crossover study in subjects with normal renal function or with mild, moderate, or s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
27
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 25 publications
(30 citation statements)
references
References 13 publications
2
27
1
Order By: Relevance
“…Safety assessments included evaluation of treatmentemergent adverse events (TEAEs), clinical laboratory results (hematology [including coagulation], serum chemistry [including liver function parameters], and urinalysis), vital sign measurements (blood pressure, heart rate, and body temperature), 12-lead electrocardiographic measurements, and physical examination findings. Safety from period 3 (oral delafloxacin, no SBECD) has previously been discussed 7 and is not reviewed in this article.…”
Section: Safety Assessmentsmentioning
confidence: 99%
See 2 more Smart Citations
“…Safety assessments included evaluation of treatmentemergent adverse events (TEAEs), clinical laboratory results (hematology [including coagulation], serum chemistry [including liver function parameters], and urinalysis), vital sign measurements (blood pressure, heart rate, and body temperature), 12-lead electrocardiographic measurements, and physical examination findings. Safety from period 3 (oral delafloxacin, no SBECD) has previously been discussed 7 and is not reviewed in this article.…”
Section: Safety Assessmentsmentioning
confidence: 99%
“…This study was designed to characterize the pharmacokinetics and tolerance of SBECD in subjects with renal impairment, including subjects with end‐stage renal disease (ESRD) undergoing hemodialysis. Delafloxacin pharmacokinetics, as well as overall safety from this study, has been previously reported . This analysis specifically assesses SBECD pharmacokinetics and safety in patients with varying degrees of renal impairment.…”
mentioning
confidence: 92%
See 1 more Smart Citation
“…Details of the study design have been previously reported as well as the pharmacokinetic and safety/tolerability results from subjects with mild, moderate, and severe impairment compared to subjects with normal renal function. 7,8 The subjects with ESRD participated in 2 treatment periods that were separated by a washout period of at least 14 days. Subjects were administered a 1-hour IV infusion of 300 mg delafloxacin approximately 1 hour before initiation of hemodialysis (period 1) or after completion (period 2) of the last hemodialysis session of the week.…”
Section: Methodsmentioning
confidence: 99%
“…6 A study of the effect of mild, moderate, and severe renal impairment on the pharmacokinetics (PK) of a single dose of IV and oral delafloxacin showed that delafloxacin total clearance decreased as the degree of renal function worsened. 7,8 Renal clearance of delafloxacin in severe impairment was 0.44 L/h compared to 6.03 L/h in subjects with normal renal function. Delafloxacin total exposure expressed as area under the plasma concentration-time curve (AUC) in severely renal-impaired subjects was approximately twice that of those with normal renal function regardless of route (IV or oral) of administration, with maximum exposure (C max ) being similar across the renal function groups (mild, moderate, and severe).…”
mentioning
confidence: 98%